À MESA COM JAIME II, O JUSTO: SAÚDE, ALIMENTAÇÃO E PODER NA COROA DE ARAGÃO ENTRE OS SÉCULOS XIII E XIV - Amatuzzi, Renato Toledo Silva (2016)
In the middle age, in Latin East, remarkable for political theory of the organic metaphor, it was formulated by Jhon of Salisbury, in the Policraticus. This theory imagined the society like a living organismo, whose head would be the king. All the members of social body should exercise their roles way consoante and efficient. However when the king got sick, all the society got sick too. In the Aragon´s kingdom, in 1308, the king Jaime II, the Virtuous, avoiding a political crises asked for help for his doctor, Arnaldo de Vilanova, to heal his sickness, the hemorrhoid. Based on medicals and hygiene theories, Arnaldo noticed in the food functionality the way to cure the king´s sckiness. Through the food list his showed there were the besto f the territory, the doctor selected, blended and recomended a loto f types of food and tastes. This research has the propouse to anlyze the difusion of medical theories in Aragon´s kingdom between XIII and XIV centuries trought the healths rules and understand too the relationship between the doctor´s craft and cook´s craft, revealing a fet up table where taste and health were importante allies to the health´s king.